Risk Minimization of Financial Assets Portfolio - El Hachlouf, Mostafa; El Haddad, Mohammed; Hamza, Faris; Aboulethar, Meriem (International Journal of Economics and Financial Issues, 2019)
The minimization of the portfolio of financial assets has a particular interest in the field of finance. In this context, several approaches have been proposed to contribute to the solution of this problem which Markowitz approach is the most popular. In this paper, we propose a new approach to minimize the risk of portfolio that measured by a value at risk (VaR) using neural networks. The assets of this portfolio are invested in a market which the fluctuations follow a normal distribution. The minimization procedure is done after the calculation of mathematical explicit formula of Value at Risk (VaR) using the Black-Scholes stochastic process for these portfolios, whichits structure remains constant over the considered time horizon. Keywords: Value at Risk; Neural Networks; Portfolio Risk; Black-Scholes; Stochastic Process; Normal Distribution. JEL Classifications: C61;C63;C15